PERAN ORANGTUA DALAM PENGAJARAN BAHASA INGGRIS MELALUI APLIKASI DIGITAL PADA ANAK USIA DINI (Studi Kasus di TK Al Munawwarah Bandung) - Nurrahma Primiani; Fauziyyah Sahar (ADISAM PUBLISHER, 2025)
This study entitled “Pembelajaran Bahasa Inggris pada Anak Usia Dini di TK Al-Munawwarah Bandung” investigates how English has grown and developed, as well as been used by pre-school children (at the age of 4-6 years old). Through this study, pre-school children are shown to have abilities to absorb and learn English (as their non first language) through learning applications, such as Lingokids, Duo Lingo, Easy Peasy, and so on. This is done by children as a way for them to explore their language skill and communicate with each other. This article argues that pre-school children, at the same time, are shown to be able to adapt to two things, namely the progress of the times and formal/traditional education patterns (Kindergarten). The data used in this study is a survey of student’s parents regarding of their children's language progress. From the data analyzed, it was found that the process of filtering English learning application downloads must be under the supervision of parents as the child's front guard